2013
DOI: 10.1042/bj20130101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the first synthetic inhibitors of the type II transmembrane serine protease TMPRSS2 suitable for inhibition of influenza virus activation

Abstract: TMPRSS2 (transmembrane serine proteinase 2) is a multidomain type II transmembrane serine protease that cleaves the surface glycoprotein HA (haemagglutinin) of influenza viruses with a monobasic cleavage site, which is a prerequisite for virus fusion and propagation. Furthermore, it activates the fusion protein F of the human metapneumovirus and the spike protein S of the SARS-CoV (severe acute respiratory syndrome coronavirus). Increased TMPRSS2 expression was also described in several tumour entities. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
135
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 57 publications
1
135
0
3
Order By: Relevance
“…Calu-3 cells infected with H1N1 or H3N2 influenza viruses were treated with I-432 and related TMPRSS2 inhibitors at 50 mM for 48 h incubation time and it was found that the viral replication was significantly reduced. So far, the most potent inhibitor for suppression of H1N1 and H3N2 influenza viral spread in Calu-3 cells is I-432, which was also applied in our present study 17 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calu-3 cells infected with H1N1 or H3N2 influenza viruses were treated with I-432 and related TMPRSS2 inhibitors at 50 mM for 48 h incubation time and it was found that the viral replication was significantly reduced. So far, the most potent inhibitor for suppression of H1N1 and H3N2 influenza viral spread in Calu-3 cells is I-432, which was also applied in our present study 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of HA cleavage and the inhibition of influenza virus spread in TMPRSS2-expressing MDCK cells by treatment with hydrophobic decanoylated peptide mimetic protease inhibitor, I-3 was observed after exposure of cells to A/Hamburg/09 (H1N1) 14,16 . I-432 was found to be one of the most potent 3-amidinophenylalanine-derived inhibitors of TMPRSS2 and matriptase 17 and it was also shown that I-432 at 50 mM did not affect cell viability in IPEC-J2 cells after 48 h treatment 18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, effective inhibitors of matriptase could be potential drugs for these diseases and pathogenic conditions. This led to the development of various types of matriptase inhibitors including the sulfonylated 3-amidinophenylalanine derivatives [17][18][19][20][21] and the substrate-analogue ketobenzothiazole derivatives derived from the known P4-P1 Arg-Gln-Ala-Arg substrate sequence at the autocatalytic activation site of matriptase 22,23 . Another selective small molecule matriptase inhibitor, the arginal derivative CVS-3983, could suppress the growth of androgen-independent prostate tumor xenografts in vivo 24 .…”
Section: Introductionmentioning
confidence: 99%